Marsjanie. Borowczyk i Lenica na Międzynarodowym Konkursie Filmu Eksperymentalnego w Brukseli - Sitkiewicz, Paweł (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The text describes the backstage of the legendary International Experimental Film Competition in Brussels, which accompanied the Expo-58 Exhibition at a turning point of the political thaw in Eastern and Central Europe. The most important representatives of avant-garde cinema and auteur animation of three generations took part in this event. The Grand Prix was awarded to The House of Walerian Borowczyk and Jan Lenica. The prize became the ticket to a European career for these two young filmmakers. The competition was also remembered as a symbolic beginning of the “Polish school of animation” (or the so-called “Polish school of experimental film”) on the global film market. The author of the article also writes about a difficult return to Poland, about a cash prize that caused many problems, about the successes of Polish films in Brussels, and about the reception of The House in Poland and abroad. Finally, he tries to demonstrate why this bleak and difficult to understand film, which builds opposition to the optimism of Expo Exhibitions, won the main prize, beating over 300 competitors from around the world.